Theoretical Preconditions to Classify Soft Law as Part of the Legal System: The Case of Aviation Law - Stonkus, Saulius (Teisė, 2024)
This paper examines the theoretical preconditions for classifying aviation soft law as part of the legal system by distinguishing the essential characteristics of this phenomenon and analysing them within the context of different perspectives of legal understanding, presupposed by the competing binary and continuum (relative or gradual normativity) perceptions of Law, as well as the Theory of Functional Normativity.